Effects of surgery and general anaesthesia on sleep–wake timing: CLOCKS observational study. (21st August 2021) - van Zuylen, M. L.; Meewisse, A. J. G.; Ten Hoope, W.; Eshuis, W. J.; Hollmann, M. W.; Preckel, B.; Siegelaar, S. E.; Stenvers, D. J.; Hermanides, J.
Summary: Surgery and general anaesthesia have the potential to disturb the body's circadian timing system, which may affect postoperative outcomes. Animal studies suggest that anaesthesia could induce diurnal phase shifts, but clinical research is scarce. We hypothesised that surgery and general anaesthesia would result in peri‐operative changes in diurnal sleep–wake patterns in patients. In this single‐centre prospective cohort study, we recruited patients aged ≥18 years scheduled for elective surgery receiving ≥30 min of general anaesthesia. The Munich Chronotype Questionnaire and Pittsburgh Sleep Quality Index were used to determine baseline chronotype, sleep characteristics and sleep quality. Peri‐operative sleeping patterns were logged. Ninety‐four patients with a mean (SD) age of 52 (17) years were included; 56 (60%) were female. The midpoint of sleep (SD) three nights before surgery was 03.33 (55 min) and showed a phase advance of 40 minutes to 02.53 (67 min) the night after surgery (p < 0.001). This correlated with the midpoint of sleep three nights before surgery and was not associated with age, sex, duration of general anaesthesia or intra‐operative dexamethasone use. Peri‐operatively, patients had lower subjective sleep quality and worse sleep efficiency. Disruption started from one night before surgery and did not normalise until 6 days after surgery. We conclude that there is a peri‐operative phase advance in midpoint of sleep, confirming our hypothesis that surgery and general anaesthesia disturb the circadian timing system. Patients had decreased subjective sleep quality, worse sleep efficiency and increased daytime fatigue.